Comportamento adaptativo e perspectivação do futuro: algumas evidências nos contextos da educação e da saúde - Carvalho, R. G.; Pocinho, M.; Silva, C. (Psicologia-Reflexão e Crítica, 2010)
The role of future in the current individual behavior, especially among youngsters, has been receiving considerable attention. It is important to underline the consistent effect of association between future plans construction and perspectives - as expressed by the Future Time Perspective (FTP) concept and adaptive behavior expression. This aspect is considered as a contributor to higher adaptation. Two of the contexts where that relation is studied are education and health, the latter specifically at healthy behavior development and risk prevention levels. Having in mind these two dimensions, the present article intends, to discuss some data from several studies, which are considered rele-vant for giving emphasis on such